Ca14-3-3 Interacts With CaWRKY58 to Positively Modulate Pepper Response to Low-Phosphorus Starvation - Cai, Jinsen; Cai, Weiwei; Huang, Xueying; Yang, Sheng; Wen, Jiayu; Xia, Xiaoqin; Yang, Feng; Shi, Yuanyuan; Guan, Deyi; He, Shuilin (Frontiers in Plant Science, 2021)
Low-phosphorus stress (LPS) and pathogen attack are two important stresses frequently experienced by plants in their natural habitats, but how plant respond to them coordinately remains under-investigated. Here, we demonstrate that CaWRKY58, a known negative regulator of the pepper (Capsicum annuum) response to attack by Ralstonia solanacearum, is upregulated by LPS. Virus-induced gene silencing (VIGS) and overexpression of CaWRKY58 in Nicotiana benthamiana plants in combination with chromatin immunoprecipitation and electrophoretic mobility shift assays demonstrated that CaWRKY58 positively regulates the response of pepper to LPS by directly targeting and regulating genes related to phosphorus-deficiency tolerance, including PHOSPHATE STARVATION RESPONSE1 (PHR1). Yeast two-hybrid assays revealed that CaWRKY58 interacts with a 14-3-3 protein (Ca14-3-3); this interaction was confirmed by pull-down, bimolecular fluorescence complementation and microscale thermophoresis assays. The interaction between Ca14-3-3 and CaWRKY58 enhanced the activation of PHR1 expression by CaWRKY58, but did not affect the expression of the immunity-related genes CaPR1 and CaDEF1, which are negatively regulated by CaWRKY58 in pepper upon Ralstonia solanacearum inoculation. Collectively, our data indicate that CaWRKY58 negatively regulates immunity against Ralstonia solanacearum, but positively regulates tolerance to LPS and that Ca14-3-3 transcriptionally activates CaWRKY58 in response to LPS.